Asymptotic solutions for the two-centre coulomb continuum problem - Kh, Tsookhuu; J, Madsen; O, Chuluunbaatar; N, Tsogbadrakh (Scientific transaction of the National University of Mongolia. Physics, 2022)
The understanding and modelingof electrons moving in the fileds of wtwo fixed charges plays an important role in electron-molecule, slow meson-atom collisions and more generally in deflection experiments.